Solitudes of the workplace : women in universities - Whittaker, Elvi W (McGill-Queen's University Press, 2015)
Solitudes of the Workplace focuses on experiences of marginalization, uncertainty, and segregation created by the hierarchical structures of categories in universities and by gendered identities. Studying a wider range of women's roles in universities than prior research, the experiences of support staff, senior administrators, researchers, non-academic administrators, and contract teachers are added to those of faculty and students. These essays show how attempts to introduce new knowledge are manoeuvred and the resistance this process can encounter, as well as the ways in which institutional policies can blur and change identities. Addressing longstanding issues such as the entanglement of gender and the assessment of merit, attention is also given to how new identities are claimed and successfully projected. Essays presenting workers' points of view reveal the confusion that occurs when official policy and everyday knowledge conflict, when processes like tenure and other status changes create troublesome realities, and when it becomes routine to experience status denigration. Within the social order of the university and its existing boundaries, gender issues of past decades sometimes surface, but all too often remain an unspoken presence. Solitudes of the Workplace is a revealing look at the isolating experiences and inequities inherent in these institutional environments.